Monitoring intra-annual cambial activity based on the periodic collection of twigs - a feasibility study - Luz, Ana Luísa; Pereira, Helena; Lauw, Alexandra; Leal, Sofia (Dendrochronologia, 2014)
This study aims at monitoring the cambial activity and xylogenesis along the growing season under Mediterranean climate using a newly designed sampling method based on the periodic collection of twigs from the crown, in order to test its efficacy. Ten species were selected; seven hardwood (Acer pseudoplatanus L.,Ceratonia siliqua L., Schinus terebinthifolius Raddi, Olea europaea L., Fraxinus angustifolia Vahl, Populus alba L., Quercus suber L.) and three softwood species (Abies alba Mill., Cupressus sempervirens L., Pinus pinea L.). The twigs were collected monthly during one year. After microtome sectioning and staining, the sections were photographed and analyzed to monitor ring development and the period of cambial activity. The twigs revealed large differences in radial growth, within and among species, which might be associated to their particular position in the tree, to the effect of the different crown microclimates, and/or to the crown conformation and type of leaves. The method showed effectiveness in the study of cambial activity, but limitations in the study of ring development due to impossibility of comparing samples. Improvements to the method are proposed, aiming essentially at minimizing the variability among samples.
Keywords: cambial activity; Dendrochronology; growth-ring; Mediterranean; twig sampling